Ebrei nella Terraferma veneta del Quattrocento - Mueller, Reinhold C. (Reti Medievali E-Book, 2005)
This book is a collection of the proceedings of the study seminar held in Verona on 14 November 2003. This was the occasion for the presentation of the results of archive research performed by young researchers on the Jewish presence in numerous cities and smaller towns of the Venetian hinterland in the fifteenth century (Vicenza, Verona, Treviso, Feltre, and the minor centres of the Polesine and Verona and Vicenza territory). The various themes that are developed though attentive and documented analysis include: the autonomous initiative of the civic communities in the relation with the Jewish moneylenders and the attitude of Venice, divided between protection and the anti-Jewish tensions that were widespread among the lagoon nobility; the encounter and dialectic between the Ashkenazi and Italian components in the communities settled within the cities and hamlets of Veneto; the difference of the social and cultural climate between the first and second half of the fifteenth century, marked by incisive Franciscan preaching and attempts at expulsion from the cities; a look 'from the inside' which opens up the role of women in the economic life of the Jewish communities. Over twenty years after the convention on 'The Jews and Venice' promoted by the Fondazione Cini, these contributions illustrate the revival of study and the ever-present need for comparison and exchange on the issue of the Jewish presence in Italy.